Peningkatan Kualitas Produk Kerajinan Anyaman Eceng Gondok melalui Inovasi Mesin Pelurus Kawat Sederhana - Intan Berlianty; Irwan Soejanto; Yuli Dwi Astanti; Farah Amalia Fajri; Eflita Win Zahri (Pusat Riset dan Inovasi Nasional, 2025)
The utilization of water hyacinth (Eichhornia crassipes) as a raw material for woven handicrafts has become an environmentally friendly economic activity in several rural communities in Indonesia. However, one of the persistent challenges in the production process lies in the preparation of the wire frame, which functions as the main structural support for shaping the product. Manually straightening wire is labor-intensive, inconsistent, and ergonomically harmful, especially for women artisans. This community service initiative aimed to improve the quality and efficiency of water hyacinth woven products through the introduction of an appropriate technology innovation: a manually operated wire straightener machine. The design was developed based on participatory ergonomics principles and tested in a home-based handicraft production setting in Banyumas, Central Java. The implementation involved tool handover, training, and evaluation of its impact on product quality and work comfort. Results showed a significant improvement in wire straightness, reduced physical fatigue among artisans, and better structural consistency of the final products. The findings demonstrate that simple ergonomic innovations can effectively enhance artisanal productivity and occupational well-being. This initiative has the potential to be replicated in other craft-based communities to support sustainable microenterprise development.